Rhabdomyolysis after Hand Assisted Laparoscopic Donor Nephrectomy: Calgary’s experience - Rochon, Ryan; Monroy, Mauricio; Yilmaz, Serdar (Journal of Surgical Sciences, 2019)
Background: Rhabdomyolysis is a post-operative complication resulting from skeletal muscle injury during the surgery. The true incidence of rhabdomyolysis in laparoscopic living donor nephrectomy is unknown due to a paucity of evidence in the literature. Rhabdomyolysis can have serious short-term and long-term consequences for the living kidney donors. There have been a number of risk factors identified that may increase the risk of rhabdomyolysis. Materials and Methods: Our program has offered a hand assisted laparoscopic donor nephrectomy approach for our donors since 2001.We have performed 209 kidney transplants using this approach. The institution’s database was searched for postoperative complications. Three donor patients with post-operative rhabdomyolysis were identified. Results: All three patients were young healthy males. The operative times were all greater than four hours. Fortunately, all three patients were recognized early and received treatment promptly. Dialysis was not required and no long-term renal dysfunction occurred. Conclusion: Rhabdomyolysis is an uncommon post-operative complication following hand assisted laparoscopic living donor nephrectomy. We have a high index of suspicion for rhabdomyolysis to promptly recognize this rare but potentially serious complication after any operation lasting greater than 4 hours. Creatinine Kinase levels have been implemented at our centre for all living kidney donors. Journal of Surgical Sciences (2015) Vol. 19 (2) : 44-47